2012
DOI: 10.1001/archpediatrics.2012.1028
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Intensity and Cardiometabolic Risk in Youth

Abstract: To determine the association between physical activity (PA) intensities and cardiometabolic risk factors in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 37 publications
12
111
2
3
Order By: Relevance
“…Mark and Janssen (2008) found a favourable dose-response gradient Diastolic BP: associations were favourable (6/8 studies; Andersen et al 2006;Ekelund et al 2006;Mark and Janssen 2008;Owen et al 2010;Chaput et al 2013;Knowles et al 2013), null (1/8 studies; Leary et al 2008), or mixed (favourable and null; 1/8 studies; Hurtig-Wennlof et al 2007). Mark and Janssen (2008) found an inverse dose-response gradient Mean arterial BP: null association (1/1 studies; Hjorth et al 2014a) VPA: High-normal systolic BP %: was greatest in the lowest tertile of VPA (1/1 studies; Hay et al 2012) BP z score: no association (1/1 studies; Stabelini Neto et al 2014) …”
Section: No Serious Imprecisionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mark and Janssen (2008) found a favourable dose-response gradient Diastolic BP: associations were favourable (6/8 studies; Andersen et al 2006;Ekelund et al 2006;Mark and Janssen 2008;Owen et al 2010;Chaput et al 2013;Knowles et al 2013), null (1/8 studies; Leary et al 2008), or mixed (favourable and null; 1/8 studies; Hurtig-Wennlof et al 2007). Mark and Janssen (2008) found an inverse dose-response gradient Mean arterial BP: null association (1/1 studies; Hjorth et al 2014a) VPA: High-normal systolic BP %: was greatest in the lowest tertile of VPA (1/1 studies; Hay et al 2012) BP z score: no association (1/1 studies; Stabelini Neto et al 2014) …”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…m The quality of the evidence from longitudinal studies was downgraded from "low" to "very low" because of serious risk of bias in 3 studies that diminished the level of confidence in the observed effects. n Includes 47 cross-sectional studies (Brage et al 2004a(Brage et al , 2004bGutin et al 2005b;Wennlof et al 2005;Andersen et al 2006;Ekelund et al 2006Ekelund et al , 2009Hurtig-Wennlof et al 2007;Quiros-Tejeira et al 2007;Rizzo et al 2007Rizzo et al , 2008Butte et al 2007b;Ruiz et al 2007;Leary et al 2008;Mark and Janssen 2008;Sardinha et al 2008;Sakuragi et al 2009;Schofield et al 2009;LeBlanc and Janssen 2010;Nguyen et al 2010;Owen et al 2010;Carson and Janssen 2011;Holman et al 2011;Moreira et al 2011;Colley et al 2012;Hay et al 2012;Hearst et al 2012;Henderson et al 2012;Jimenez-Pavon et al 2012, 2013b, 2013cMartinez-Gomez et al 2012;Mota et al 2012;Mendoza et al 2012;Barreira et al 2013;Carson et al 2013;Chaput et al 2013;Janssen et al 2013;Lamotte et al 2013;Knowles et al 2013;…”
Section: Mpamentioning
confidence: 99%
See 3 more Smart Citations